A Taxonomy of Fallacies in System Safety Arguments - Knight, John; Greenwell, William; Holloway, Michael (University of Virginia, Department of Computer Science, 2005)
A systems safety argument is intended to show that the system is acceptably safe to operate in a given environment. If that argument is fallacious, the system may be prone to hazardous modes of operation that could contribute to accidents. We conducted a case study of three industrial safety cases to determine the frequency and nature of fallacious reasoning in system safety arguments. Our results suggest that the fre- quency of logical fallacies in these arguments is significant and that they follow common themes. To avoid these fallacies, developers must be aware of them when they create safety arguments, and regulators and investigators must know how to discover them when they review those arguments. We present a taxonomy of logical fallacies tailored to system safety cases to assist developers and regulators in these tasks and then demonstrate the taxonomy by applying it to the three safety cases from our case study.
Original submission date: 2012-10-29T19:42:45Z